Study on present status of dairy farming at sadar upazila of Rangpur district (Research in Agriculture Livestock and Fisheries, 2023)
This study was conducted to investigate the present status of dairy farming through a field survey at Rangpur Sadar Upazila, Rangpur, Bangladesh from December 2020 to December 2021. A total of 14 indigenous and 95 crossbred cows were selected randomly from the selected dairy herds. The results indicated that most of the farmers were male (25-35 years) and 17.24% of farmers involved in dairy farming were graduated. With regards to the housing system, the percentage of rearing system was found equal and the majority of the farmers could not afford fodder cultivation (70%). In the case of cross-breed animals like HF cross the farmers provided green grass and concentrate in a high amount of 11.03±0.76 kg and 4.82±0.33 kg per animal per day respectively. Likewise, straw feeding was found higher in indigenous animals (06.64±0.55 kg/animal/day). Most of the farmers followed AI (91.7%) with frozen semen (99.08%) for reproduction purposes in which 37.61% of cows need double services for conception. The age of first puberty was lower (19.97±0.57 months) in HF cows. In contrast, the average number of services per conception was lower in indigenous cows which was 1.95±0.14. The average milk yields of indigenous, HF, and SL crossbred cows were 2.36±0.118, 15.07±0.457and 3.2±0.287 L/day/cow, respectively. However, enhancing the availability of feeds and fodder, the proper market price of milk, and minimization of veterinary costs might improve dairy production in the study area as well as in other districts of Bangladesh.Res. Agric. Livest. Fish. 10(1): 83-90.